Meningitis due to Gemella sp. in a patient with severe ENT conditions: case report and review of the literature - Ilyès Benhalima; Lola Jacquemont; Laurine Milière; Alina Tone; Nicolas Ettahar; Gisèle Dewulf; Edith Mazars (Annals of Clinical Microbiology and Antimicrobials)
Abstract In June 2022, a 73-year-old man with a history of laryngeal and esophageal carcinoma was admitted to the emergency unit with sudden fever, confusion, and general condition deterioration. Initial assessments showed a fever of 38.5 °C, elevated C-reactive protein (CRP) at 209 mg/L, and a neutrophil count of 10.4 G/L, with negative results for urine analysis, blood cultures, and multiple infectious pathogens, including Legionella pneumophila, pneumococcal antigen, and SARS-CoV-2. Computed tomography (CT) scans revealed no significant infectious focus. Empirical treatment with Ceftriaxone and Ciprofloxacin was initiated. Despite treatment, the patient’s condition remained unchanged, and a lumbar puncture revealed turbid cerebrospinal fluid (CSF) with 14,300 white blood cells (WBC)/mm³, predominantly neutrophils, elevated proteins, and decreased glucose. Gram staining suggested Neisseria meningitidis, but further testing was necessary. Antibiotic therapy was switched to Cefotaxime and Dexamethasone, and the patient was transferred to the Tropical and Infectious Disease Unit. Multiplex PCR assays and additional CSF tests were negative for common pathogens. Sequencing of 16S ribosomal RNA identified Gemella sp. The patient’s condition improved with continued Cefotaxime treatment, and he recovered without neurological sequelae. Subsequent dental CT revealed poor dental hygiene but no signs of osteo-meningeal breach or bone lysis. A literature review identified 22 reported cases of central nervous system (CNS) infections caused by various Gemella species from 1980 to 2022. Of these, 59% presented with meningitis, and 41% had additional encephalitis or brain abscesses. Complete recovery occurred in 77% of cases, with 9% resulting in neurological damage and another 9% in fatal outcomes. Relapses occurred in 14% of the cases. The review highlighted that CNS infections by Gemella spp. primarily affect immunocompromised adults with ENT (ear nose throat) or neurological breaches, although some cases involved healthy individuals. This case underscores the diagnostic challenges posed by uncommon pathogens like Gemella and highlights the utility of molecular microbiology in identifying causative agents, thus guiding appropriate treatment. The patient’s history of ENT and esophageal cancers, along with recent radiotherapy and chemotherapy, likely contributed to the infection’s development. The case emphasizes the importance of thorough investigation in febrile confusion cases and the potential role of Gemella spp. in CNS infections.